Strategi internasionalisasi bahasa Indonesia melalui program BIPA - Pradicta Nurhuda; Siti Drivoka Sulistyaningrum; Liliana Muliastuti (Jurnal Bahasa Indonesia bagi Penutur Asing, 2023)
Efforts to internationalize the Indonesian language are implicitly stated in Law Number 24 of 2009 Article 32, Section 2 which says that the Indonesian language can be used in international forums abroad. This study aims to describe strategies that can be used to internationalize Indonesian through the BIPA program. This study used a qualitative research method with a literature study approach. The results of the study show that strategies that can be implemented include (1) developing BIPA institutions in every country that has diplomatic relations with Indonesia; (2) internalization of Indonesian cultural material in BIPA material; (3) internalization of Indonesian music material in BIPA material; and (4) obliging UKBI for foreigners who will work or study in Indonesia.